1987
DOI: 10.1590/s0036-46651987000300009
|View full text |Cite
|
Sign up to set email alerts
|

Fiebre "Q" en Uruguay

Abstract: Los autores hacen una revisión de la problemática referida a la fiebre Q, tanto desde el punto de vista clínico como epidemiológico. El primer caso nacional se comunicó en el año 1956, en un adulto, obrero de frigorífico. En 1966 se comunica el primer caso en un niño. A partir de esa fecha se realizan varias encuestas serológicas en humanos y en animales. En seres humanos los hallazgos varían entre 4.2% y 5.5% según el año estudiado. En animales se hallaron valores que oscilaron entre 0.9% (animal para abasto)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 8 publications
0
9
0
5
Order By: Relevance
“…These results suggest that C. burnetii is a previously undiagnosed cause of abortion in dairy cattle in Uruguay and highlight the importance of examining the placenta in aborted cattle to achieve this diagnosis. The presence of antibodies against C. burnetii in slaughterhouse workers from Uruguay has been associated with history of clinical signs, and a clinical case of endocarditis (Moreira et al 1987), showing that this agent is an occupational hazard for veterinarians and slaughterhouse workers. Also, antibodies against C. burnetii have been found in different animal species in this country, including cattle (Moreira et al 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that C. burnetii is a previously undiagnosed cause of abortion in dairy cattle in Uruguay and highlight the importance of examining the placenta in aborted cattle to achieve this diagnosis. The presence of antibodies against C. burnetii in slaughterhouse workers from Uruguay has been associated with history of clinical signs, and a clinical case of endocarditis (Moreira et al 1987), showing that this agent is an occupational hazard for veterinarians and slaughterhouse workers. Also, antibodies against C. burnetii have been found in different animal species in this country, including cattle (Moreira et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of antibodies against C. burnetii in slaughterhouse workers from Uruguay has been associated with history of clinical signs, and a clinical case of endocarditis (Moreira et al 1987), showing that this agent is an occupational hazard for veterinarians and slaughterhouse workers. Also, antibodies against C. burnetii have been found in different animal species in this country, including cattle (Moreira et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…C. burnetii infection has been reported in serosurveys of more than 30 years ago (Ribeiro-Neto et al 1964, Riemann et al 1974, 1975 but since then, no information of such infection has been available from Brazil. Q fever has been reported Southern (Moreira et al 1989) and Northern Brazil (Tran et al 2002) but for inexplicable reasons little attention has been paid to it, not withstanding the fact that it is supposed to be a worldwide zoonosis presents everywhere (Casolin 1999, CDC 2004. The findings here reported along with the recent report of a human case-series (Costa 2004) demand the inclusion of Q fever among the causative agents of human infections in this region.…”
Section: Discussionmentioning
confidence: 99%
“…14 Several studies have confirmed the presence of antibodies against C. burnetii in human and animal populations in South America, indicating that the organism is present on the continent. 13,35 One study from Brazil established the presence of the agent in a human clinical case associated with PCR-positive animals. 31 In Uruguay, the presence of antibodies against C. burnetii in slaughterhouse workers has been associated with a history of clinical signs, and a clinical case of endocarditis, 35 showing that this agent is an occupational hazard for slaughterhouse personnel.…”
mentioning
confidence: 99%